Prevalence Of cardiovascular risk factors among Sabah health offices employees in 2008 - Mohammad Saffree Jeffree; Richard Avoi (2011)
Introduction: Prevalence of cardiovascular risk factors is increasing among the general population, but little is known about employee's risk factor who works in the health office. The objective was to assess the prevalence of cardiovascular risk factors among health office employees and relationship to other contributing factors. Method: Cross sectional data were obtained from Feb-March 2008 as part of the non-communicable disease employee screening program. Universal sampling method was used. 341 employees were agreed to participate in Sabah state health offices. Data was collected through a questionnaire on risk factors, anthropometric and blood pressure measurement, random blood glucose and cholesterol analyses. Data was analyzed using SPSS version 15.0 and presented by descriptions, univariate and multivariate analyses for significant risk factors. Results: The response rate was 96.6%. The prevalence of raised blood pressure (17.9%,[95%Cl:14.1-22.5]), blood cholesterol (21. 7%, [95%CI: 17.5-26. 5]), blood glucose (10.0%, [95%Cl:7.1-13.8]), smoking (17. 3%, [95%CI: 13. 5- 21.8]), physical inactivity (29.6%,[95%Cl:24. 9-34.8]) and drink alcohol (9. 7%,[95%Cl:6. 9-13. 5]) were lower than general population studies in the National .Morbidity Survey Report Ill and Malaysian NCO surveillance of 2006. The prevalence of Overweight (BMI